Poster presentation Culturable bacterial and fungal communities of the seagrass Posidonia oceanica of Cyprus as potential laccases producers - Vasquez Christodoulou, Marlen (My University, 2026)
Modestou C, Georgiou T, Pantelides I, Tsolakidou MD, Tampouri E, Markou M, Antoniadis K, Palates P, Vasquez MI, Culturable bacterial and fungal communities of the seagrass Posidonia oceanica of Cyprus as potential laccases producers, Poster presentation, 6th European Bioremediation Conference (EBC-VI), Chania, Greece, 29 June-2 July 2015.